“YES, I WILL WORK ON MY FREE TIME” – DIGITAL WORK ON AMAZON MECHANICAL TURK AS THE HISTORICAL CONTINUATION OF THE EXPLOITATION OF WOMEN'S LABOR - Moreschi, Bruno; Jurno, Amanda; Lemos, Monique (AoIR Selected Papers of Internet Research, 2021)
In this proposal, we pursue an approximation to Amazon Mechanical Turk (AMT) women workers to understand their specificities and their layers of dependence in this environment so pertinent to the “late capitalism” (Crary 2016). AMT is an online platform where workers perform low-paid services that cannot be efficiently automated. Since 2019, in the Group [Anonymized excerpt], at the University [Anonymized excerpt], we have carried out projects where we approach these workers in an attempt to understand their routines, desires and the future of work itself. In our experiences, it has become evident that women turkers tend to be even more precarious due to gender issues passed to AMT. Also we concluded that AMT help keeping the women labor power available for unpaid domestic services and, at the same time, make it profitable for several companies. To understand more about them, we conducted a survey with 53 women turkers and systematized their responses. We approached some of them to understand the relationship between Artificial Intelligence and gender issues, and also ways of better working conditions and more autonomy for these women workers.